IDEOLOGICAL DIALECTICS OF POST-SOVIET NATIONALISM - Berekashvili , Bakar (The Copernicus Journal of Political Studies, 2021)
This article is an attempt at a critical examination of the ideological nature of nationalism in the post-Soviet world, with particular focus on the Georgian experience. Social, political, cultural and economic changes which took place in Georgia after the Soviet Union’s dissolution also aimed to change the society’s mental structure. In this context, the idea of nationalism is a way to reorganize politics and society. Nationalism in post-Soviet Georgia is accommodated in the paradigm of new ideological hegemony. Liberalism and conservatism considered as alternatives to communism have become the principal ideological dialectics of post-Soviet nationalism, which also mirrors the general ideological orientation of nationalism in post-Soviet societies. Also, political-ideological instrumentalization of nationalism has been aimed at strengthening political positions and privileges of the new ruling class, while it has also played one of the central roles in the political and cultural process of power struggle. This article sheds light on the major issues of ideological hegemony and reconstruction of nationalism in a changing post-Soviet society.